Feeding silkworms with HPMC dispersed MoO2 NPs: An efficient strategy to enhance the supercapacitance performance of carbonized silk. (20th October 2021) - Liang, Jianwei; Zhang, Xiaoning; Ji, Yansong; Chen, Zhenyu; Norton, Michael L.; Wang, Yixuan; Yan, Chi; Zheng, Xi; Zhu, Yong; Cheng, Guotao
Abstract: It was found in our previous study that feeding silkworms with MoO2 nanoparticles (NPs) as a food additive enabled the incorporation of MoO2 NPs into the as-spun silk, which, in turn, can be used to build electrodes for energy storage. However, aggregation of the MoO2 NPs was observed at high fractional feeding dosages. In order to disperse the MoO2 NPs in fibrous silk and enhance the specific capacitance of the carbonized silk more effectively, a 0.5% (w/v) hydroxypropyl methyl cellulose (HPMC) solution was utilized as the dispersant in this work. Transmission electron microscopy (TEM) results confirmed that HPMC increased the separation of MoO2 nanoparticles incorporated within the silk matrix. Furthermore, the electrochemical performance was characterized, revealing that the specific capacitance of carbonized silk from this HPMC-MoO2 NP feeding group reached 456 F/g, compared to the value of 245 F/g from the previous study, at a current density of 0.2 A/g, demonstrating a significant improvement. The feasibility of utilizing HPMC to maintain the segregated state of MoO2 NPs throughout all stages of silk encapsulation, with negligible impact of this feeding regimen on the growth of silkworms, is demonstrated in this work. Graphical abstract: Image 1 Highlights: Upon in vivo feeding, HPMC can ensure the separation of nanoparticles even after they are encapsulated within silk fibers. Feeding HPMC to the silkworm enhances the degree of graphitization of the carbonized silk. Compared with previous results, the specific capacitance of the carbonized silk increased from 245 F/g to 456 F/g. Our work produced a silk precursor with potential utility as a high-power supercapacitor component.